Population biology and evolutionary genetics of southern right whale (Eubalaena australis) - Nevečeřalová, Petra (Univerzita Karlova, Přírodovědecká fakulta, 2023)
Southern right whale (Eubalaena australis) is a species from the Balaenidae family with a range in the southern hemisphere, which evolved in connection with Neogene climate oscillations. Its population biology involves migration between coastal waters of South America, southern Africa, Australia and New Zealand to its high-latitude foraging and feeding grounds in the Southern Ocean. Intensive historical hunting from the 18th to 19th century has impacted the population dynamics of baleen whales substantially. After the whaling moratorium, the species has been recovering from the heavy exploitation, however, recently it is facing anthropogenic changes, such as climate change. The South African population, considered to be the largest one globally and intensively studied for the last several decades, is showing an increase in the calving interval, a decline in female condition and a dramatic shift in migration routes since 2010, possibly as a consequence of significant changes in marine food webs. Methods of molecular ecology were applied to monitor the population genetics and its dynamics not only in the context of the global population but also to compare different time periods - 1990s and 2010s. The majority of the samples were collected noninvasively in cooperation with commercial whale-watching. Velryba jižní (Eubalaena australis) je druh z čeledi velrybovitých (Balaenidae) s výhradním rozšířením na jižní polokouli, který se vyvinul v souvislosti s neogenními oscilacemi klimatu. Populační biologie tohoto druhu zahrnuje migraci mezi pobřežními vodami jižní Ameriky, jižní Afriky, Austrálie a Nového Zélandu do oblastí s vyšší primární produktivitou ve vysokých zeměpisných šířkách v Jižním oceánu. Intenzivní lov v 18. a 19. století významně ovlivnil populační dynamiku všech kosticovců. Po uvalení moratoria na komerční lov velryb se populace velryby jižní začínají zotavovat, nicméně v poslední době musí čelit antropogenním změnám, jako je změna klimatu. Jihoafrická populace, která je považována za celosvětově ...